ANALISIS PROSES REKRUTMEN DAN SELEKSI PT. UNGARAN SARI GARMEN - Saleha, Ayu Siti; Nugraheni, Krisnawati Setyaningrum (ITB AAS Indonesia Surakarta, 2025)
This research examines the employee recruitment and selection process at PT Ungaran Sari Garmen, one of Indonesia's largest export-oriented garment manufacturers. The study aims to analyze the implementation procedures of recruitment and selection, identify the challenges faced, and examine the solutions applied in addressing these challenges. This research employs a qualitative approach with data collection methods through interviews and direct observation of the recruitment and selection process, as well as documentation studies related to company profiles and employee training archives.PT Ungaran Sari Garmen implements a recruitment system that begins with workforce needs identification through a bottom-up mechanism, followed by candidate search processes through formal announcements and informal recommendation systems. A comprehensive three-week training program becomes an integral part of the selection process, with a primary focus on developing sewing skills. In its implementation, the company faces several challenges such as incomplete applicant documentation, candidate disciplinary issues during the interview process, and low interest in sewing training.To overcome these challenges, the company has developed strategic solutions including improving communication quality in requirement delivery, initial verification of candidate availability before interview scheduling, and implementing transparency in training program information. Research findings indicate that a systematic approach to recruitment and selection, supported by structured training programs and effective communication, contributes significantly to building a competent team to support company operations in the export-oriented garment industry.